2019
DOI: 10.3892/ol.2019.10250
|View full text |Cite
|
Sign up to set email alerts
|

High expression of microRNA‑500 is associated with poor prognosis in patients with acute myeloid leukemia receiving allogeneic hematopoietic stem cell transplantation

Abstract: MicroRNA-500 (miR-500) is a potential prognostic biomarker in a number of different types of cancer, such as prostate cancer and hepatocellular carcinoma. This study aimed to explore the clinical implications of miR-500 expression status in patients with acute myeloid leukemia (AML) that had received allogeneic hematopoietic stem cell transplantation (allo-HSCT). miR-500 expression status and clinical data were obtained from 74 patients with AML in the The Cancer Genome Atlas database receiving allo-HSCT. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Kaplan-Meier survival curves of OS and LFS in low and high EZH2 expression group. Moreover, for microRNAs, we observed that EZH2 expression was negatively correlated with several mi-croRNAs such as miR-21, miR-23a, miR-500, let-7a-3, miR-362, let-7eand miR-10a, which were found to be associated with AML pathogenesis and/or prognosis by previous investigations [28][29][30][31][32][33][34][35]. However, previous study demonstrated that low EZH2 protein levels correlated with poor prognosis in AML patients, which was different from our results 18.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Kaplan-Meier survival curves of OS and LFS in low and high EZH2 expression group. Moreover, for microRNAs, we observed that EZH2 expression was negatively correlated with several mi-croRNAs such as miR-21, miR-23a, miR-500, let-7a-3, miR-362, let-7eand miR-10a, which were found to be associated with AML pathogenesis and/or prognosis by previous investigations [28][29][30][31][32][33][34][35]. However, previous study demonstrated that low EZH2 protein levels correlated with poor prognosis in AML patients, which was different from our results 18.…”
supporting
confidence: 54%
“…We found that EZH2 dysregulation was significantly associated with HOX gene family, THBS1 , CDKN2B , PAX2 and H19 , which was reported highly correlated with haematopoiesis and leukaemogenesis . Moreover, for microRNAs, we observed that EZH2 expression was negatively correlated with several microRNAs such as miR‐21 , miR‐23a , miR‐500 , let‐7a‐3 , miR‐362 , let‐7e and miR‐10a , which were found to be associated with AML pathogenesis and/or prognosis by previous investigations . Of these microRNAs, miR‐506 was identified as one of the predicted microRNAs targeting EZH2 by bioinformatics, which suggested EZH2 may be a direct target of miR‐506 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Cheng et al [43] found that PFN1 knockdown can inhibit the proliferation, migration, and invasion of SGC-7901 cells by inducing G0/G1 block, and can inhibit the activation and expression of downstream ERK1/2, P38MAPK, PI3K, AKT, and mTOR. Zheng et al [44] further found that the loss of PFN1 in HSCs can lead to bone marrow failure, loss of quiescence, increased reactive oxygen species, and HSC mobilization and apoptosis in the body, and also found that PFN1 at least partially regulates the retention and metabolism of stem cells in the bone marrow through the PFN1 /Gα13/EGR1 axis. We believe that PFN1 may play an important role in promoting aging.…”
Section: Discussionmentioning
confidence: 98%
“…The post-transcriptional control of miRNA-mediated gene expression plays an important role in the selfrenewal process of HSCs [44,45] . Mitsumura et al found that knocking out miR-146b can cause the continuous activation of the NF-κB pathway and lead to the development of hematopoietic malignancies in mice after aging [46] .…”
Section: Discussionmentioning
confidence: 99%